ANALYSIS OF DISPOSAL OF GOVERNMENT-OWNED CONSTRUCTION ASSETS THROUGH SALES MECHANISM IN ASSET MANAGEMENT OPTIMIZATION (A CASE STUDY AT THE SOUTH SULAWESI REGIONAL OFFICE OF THE NATIONAL ROAD IMPLEMENTING AGENCY) - Yudhi Syarif Rachman; Syarifuddin; Amiruddin (Jurnal Ekonomi, 2023)
Optimal disposal of government assets (BMN) is necessary to reduce the burden on the state and improve efficiency. However, the disposal process is often complicated and time-consuming. Delayed disposal leads to storage issues and economic devaluation. This research aims to describe and analyze the process of disposing of 35 heavy construction equipment government assets through the auction mechanism at the South Sulawesi Regional Office of the Ministry of Public Works and Housing (BBPJN Sulawesi Selatan), identify internal and external factors that hinder the process, and analyze the mitigation actions taken by BBPJN South Sulawesi regarding these obstacles. The research method used is descriptive qualitative case study at BBPJN South Sulawesi. The results show that the disposal process of government assets through the auction mechanism at BBPJN South Sulawesi consists of 11 stages in accordance with applicable regulations and procedures. The obstacles faced include limited knowledge, outdated data, weather conditions, the Covid-19 pandemic, and the lengthy process of asset handover. BBPJN South Sulawesi has implemented several mitigation measures, such as selecting competent research teams and adjusting to the Covid-19 pandemic. Currently, the process of disposing 35 heavy construction equipment takes approximately 10 months, but with resource optimization and strong commitment, it can be completed in about 4 months.